The Effect of Quran-Recited Water Therapy on Lowering Blood Pressure among Elderlies with Hypertension - Elis Noviati; Rudi Kurniawan; Yanti Srinaryanti; Ima Sukmawati; Gita Dwi Lestari; Fidya Anisa Firdaus (Journal of Bionursing, 2023)
Background. Hypertension is a non-communicable disease that is still a global health problem. Hypertension is a condition where a person's blood pressure is 140 mmHg (systolic) and/or 90 mmHg. Apart from being a type of non-communicable disease, hypertension is also a major risk factor for other cardiovascular diseases. One way to prevent hypertension is by drinking water that has been read by the Qur'an. Objective: to determine the effect of water therapy that has been read by the Qur'an on reducing blood pressure in the elderly with hypertension in Hegarmanah hamlet, Mangunjaya district, Pangandaran district. . Methods. The method in this research is pre-experimental design with one group pretest-posttest design. Sampling in this study used a total sampling of 20 respondents with hypertension in Hegarmanah Hamlet, Mangunjaya District, Pangandaran Regency. This research was conducted in March 2022. Results. The results of the study state that there is an effect of drinking water that has been read by the Qur'an on reducing blood pressure in the elderly with hypertension in Hegarmanah Hamlet, Mangunjaya District, Pangandaran Regency, Conclusion. There is a significant relationship between water therapy reading the Qur'an on decreasing blood pressure in the elderly with hypertension because t count > t table = 16.502 > 2.093 and > p value =(0.05 > 0.00).